Polystyrene nanofibers for nonwoven porous building insulation materials. Issue 2 (5th September 2019) - Datsyuk, Vitaliy; Trotsenko, Svitlana; Peikert, Katharina; Höflich, Katja; Wedel, Nelli; Allar, Christian; Sick, Torben; Deinhart, Victor; Reich, Stephanie; Krcmar, Wolfgang
Abstract : The building industry makes a great effort to reduce energy consumption. The use of nanotechnology is one of the approaches to surpassing the properties of conventional insulation materials. In this work, an industrial cost‐effective method to manufacture highly porous materials with excellent thermal insulation properties is described. The materials are prepared from polystyrene recovered from the building sector and electrospun as nanofiber‐based sheets. Varying electrospinning parameters allow controlling the morphology of the produced materials. The materials are obtained with differences in interfiber and inner‐fiber porosity and morphology. The thermal conductivity of the freestanding and compressed materials is evaluated. Those differences affect the insulation performance: the materials with higher interfiber porosity show better thermal insulation in the freestanding state. An increase of the inner‐fiber porosity leads to better insulation in the compressed samples. Insertion of carbon nanomaterials reduces the effects of the infrared Radiation. Nanofiber‐based insulation materials from the recycled expanded polystyrene (EPS) show thermal conductivity values of 20 to 25 mW/mK (ie, 20% to 30% below the thermal conductivity of the commercial EPS). The effect of integrating polystyrene nanofiber sheets into conventional wall‐building materials is also investigated in terms of thermal insulation. The nanofiber insulation sheets are sandwiched between two pieces of the building materials resulting in a drastic increase of the insulation effect. The materials have a great potential in using, for example, as thermal insulation for the restoration of historic buildings in the narrow central parts of the old towns.